2022
DOI: 10.1002/mde.3617
|View full text |Cite
|
Sign up to set email alerts
|

Peer effects and human capital accumulation: Time spent in college and productivity in the National Basketball Association

Abstract: Starting in 2006, the National Basketball Association (NBA) set a minimum age requirement on players declaring for the draft. Consequently, elite high school players typically spend at least 1 year playing college basketball before entering the draft. This paper seeks to test for the impact of years spent in college and peer quality on NBA performance. Additional years in college are found to have an insignificant impact on persistence in the NBA at various points post draft, a positive impact on early career … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…We construct a measure of player contributions to the production of wins by NBA teams using the VORP estimate for each player i over season t . VORP represents a standard, widely used measure of the quality of an NBA player in the literature (Burdekin and Van, 2018; Humphreys and Johnson, 2020; Kaplan, 2022; Paulsen, 2022). VORP reflects an estimate of the number of points per 100 NBA team possessions that player i contributed to his team above the contribution that would be made by a replacement-level ( VORP it = − 2.0) NBA player, based on box score statistics.…”
Section: Empirical Analysismentioning
confidence: 99%
“…We construct a measure of player contributions to the production of wins by NBA teams using the VORP estimate for each player i over season t . VORP represents a standard, widely used measure of the quality of an NBA player in the literature (Burdekin and Van, 2018; Humphreys and Johnson, 2020; Kaplan, 2022; Paulsen, 2022). VORP reflects an estimate of the number of points per 100 NBA team possessions that player i contributed to his team above the contribution that would be made by a replacement-level ( VORP it = − 2.0) NBA player, based on box score statistics.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Zestcott et al (2020) and Rodenberg and Kim (2012) test for how the age of entry into the NBA impacts performance, finding an inverse relationship between age of entry and career measures of NBA performance. When looking at performance on a season‐by‐season basis and controlling for factors related to innate ability, studies have found that players with more college experience perform better early in their NBA careers, but this effect fades or reverses four or five seasons into their careers (Groothuis et al, 2007; Paulsen, 2022). Coates and Oguntimein (2010) find that college productivity measures, like assists, rebounds, and blocks per minute, are predictive of future NBA productivity.…”
Section: Literaturementioning
confidence: 99%